The Contribution of Sharia Fintech and Digital Literacy in Increasing Generation Z Interest in Accessing Sharia Financial Services in Central Java - Puti Khairani Rijadi; Yani Sukriah Siregar; Fida Arumingtyas; Mohammad Ridwan; Eko Sudarmanto (West Science Social and Humanities Studies, 2025)
The rapid development of financial technology has reshaped the delivery of financial services, including those based on Islamic principles. Generation Z, as a digitally native generation, represents a strategic segment for expanding sharia financial inclusion. This study aims to analyze the contribution of sharia fintech and digital literacy in increasing Generation Z’s interest in accessing sharia financial services in Central Java. A quantitative research approach was employed, using primary data collected through a structured questionnaire distributed to 85 respondents. The measurement instrument applied a Likert scale, and the data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The results of multiple linear regression analysis indicate that sharia fintech has a positive and significant effect on Generation Z’s interest in accessing sharia financial services. Digital literacy also shows a positive and significant influence on interest. Simultaneously, sharia fintech and digital literacy significantly contribute to increasing Generation Z’s interest in accessing sharia financial services. These findings highlight the importance of integrating sharia-compliant digital financial innovation with efforts to improve digital literacy in order to strengthen Islamic financial inclusion among young consumers. The study provides practical implications for sharia financial institutions, fintech providers, educators, and policymakers in developing strategies that align with the characteristics and needs of Generation Z.